Let g be 54⁄135 - -19*4⁄10. Suppose -4*z + 9*z - p - 16 = 0, z - p = 4. Solve 0 = -z*i + g*i + 5 for i.
-1
Let o be ((-3)/6)/(1/(-18)). Let h be (-6)/o*(-75)/2. Suppose -2*k = 4*q - 18, 3*k - 7*k = -5*q + 16. Solve -q*g = -9*g - h for g.
-5
Let j = 51 - 49. Solve -3*p + 20 = j*p for p.
4
Suppose -3*a + a = -4*w + 4, 5*a - 20 = -5*w. Solve 0 = -3*c + a + 1 for c.
1
Let x(a) be the third derivative of -a4⁄24 - 3*a3 - a**2. Let i be x(-11). Let k = i + 11. Solve -k*y - 2 = 2 for y.
-1
Let n be 16/(-10)*(1 - -4). Let z(y) = -y**2 - 9*y - 6. Let m be z(n). Solve -10 = -m*k - 2 for k.
4
Let b(q) = -2*q2 + 3 - 7*q + 0*q2 + 5 + 3*q**2. Let g be b(6). Solve -g*y = 5 - 3 for y.
-1
Let v(s) = s - 4. Let a be v(4). Suppose 2*b + a*b - 4 = 0. Let w = 2 - b. Solve o + w*o = 4 for o.
4
Let o be 4⁄5*(-10)/(-4). Suppose 0 = u - o*u. Solve u = 3*x - 2*x + 2 for x.
-2
Let s(f) = f3 + 5*f2 + 3*f - 1. Let h be s(-4). Let d = -3 + h. Solve d = w + 4*w + 15 for w.
-3